Production and Characterization of TES-EPDM Foams With Paraffin for Thermal Management Applications - Valentini, Francesco; Fambri, Luca; Dorigato, Andrea; Pegoretti, Alessandro (Frontiers in Materials, 2021)
New materials capable of storing thermal energy in view of building applications have been developed from the foaming of ethylene-propylene diene monomer (EPDM) rubber with the addition of paraffin as a phase change material (PCM) at a melting temperature of about 21°C. Considering that the EPDM foams prepared by using traditional chemical blowing agents are generally characterized by a rather elevated environmental load, the salt leaching technique has been selected (and optimized) for the production of an EPDM foam with geometrical density of 0.41 g/cm3. It has been demonstrated that the produced foams were capable of retaining up to 62 wt% of paraffin after a 38-days leaking test. The role of the absorption of paraffin on the thermal and mechanical properties of the produced foams has been investigated. The effective thermal energy of the PCM content (PCMeff) measured by differential scanning calorimetry (DSC) was 52% both in the heating and cooling scans. Shore A test, compression set (CS) test, and quasi-static compression test above and below the thermal transition of the selected PCM have been performed, and a strong dependence of materials in respect to the testing temperature has been observed, with paraffin acting as a hardener above its melting point and as a softener below its melting point. Moreover, the evaluation of the thermal energy storage (TES) performance of the foams by monitoring their surface temperature during a heating/cooling process revealed that the time required from the samples to reach the set temperature due to the presence of paraffin was three times higher in comparison to the reference sample without paraffin. Moreover, in the plateau due to paraffin melting/crystallization, heating/cooling rates of around 0.4°C/min have been found, which are much lower with respect to that of a reference sample (>1.5°C/min). Thermal efficiency and thermal intervals for the application of EPDM/paraffin have been determined in a most accurate manner and therefore have been performed DSC at a heating/cooling rate of 1°C/min. These TES-EPDM foams exhibited a thermal capacity of 120–128 J/g with an operative interval in the range from −20°C to 40°C. The produced foams were capable of maintaining their geometry after being subjected to 240 heating/cooling cycles between 0 and 40°C, and their residual TES capacity was higher than 90% for all the samples (about 95% for the materials tested on aluminum substrate). The most interesting properties for TES applications were found for the produced foams via salt leaching with 60–80 microns NaCl.